A cross-sectional study on dental surgeons’ immune status against hepatitis B virus in the Public Health System - Garbin, Clea Adas Saliba (2020)
Hepatitis B is a severe public health problem. The main world health centers have discussed it due to its pandemic proportion, high pathogenicity and infectivity. This study aimed to determine the immunization profile of dental surgeons - against hepatitis B virus (HBV) in the Public Health System (PHS) through the detection of anti-HBsAg antibodies by immunochromatography and associations with dental surgeons’ social and educational profile, factors related to professional knowledge and practices. This is a cross-sectional study on the prevalence of vaccination and immune status to HBV in dentists of Sao Paulo State PHS. Data collection occurred in three stages: questionnaire application, analysis of adhesion to the vaccination protocol and anti-HBsAg tests. Statistical analysis used the Bivariate Analysis and the Binary Logistic Regression. From the total of 219 interviewees, 74.9% reported having received three doses of the vaccine, but 35.6% were not immune to HBV. The dependent variable was associated with years in the public service (years) (OR [Odds Ratio]=1.04; 95% CI 1.00-1.08); knowledge on the subject (OR=6.93; 95% CI 1.39-34.40); incorrect answer concerning the etiological agent of the disease (OR=2.60; 95% CI 1.30-5.22); ignorance on the number of vaccine doses that have been administered (OR=3.43; 95% CI 1.14-10.30); and less than three doses of the vaccine in the immunization schedule (OR=8.76; 95% CI 3.50-21.91). A considerable portion of professionals non-immune to the HBV were found. We concluded that knowledge, years of practice and completion of the vaccination schedule (three doses) affected dental surgeons’ immune status to HBV.